Antineoplastic drugs in healthcare settings: Occupational exposure and risk graduation - Maria Francisca Portilha-Cunha; Pedro Norton; Arminda Alves; Ana R.L. Ribeiro; Adrián M.T. Silva; Mónica S.F. Santos (Emerging Contaminants)
Antineoplastic drugs (ADs) are hazardous medicinal products highlighted in the EU strategic framework on health and safety at work 2021–2027. To minimize workers' chronic exposure in oncologic settings, regular monitoring programs for these drugs are crucial and mandatory in the EU (Directive 2004/37/EC). No surveillance exists in Portugal, thus we intended to assess environmental contamination and to perform occupational exposure and risk graduation in a Portuguese tertiary hospital. Wipe sampling and liquid chromatography–tandem mass spectrometry were employed to analyze thirteen drugs of concern (bicalutamide, capecitabine, cyclophosphamide, cyproterone, doxorubicin, etoposide, flutamide, ifosfamide, imatinib, megestrol, mycophenolate mofetil, paclitaxel, prednisone), eight for the first time worldwide, in 152 surface samples over three sampling campaigns. Surface contamination before general cleaning (worst-case scenario) was higher and more widespread in the pharmacy (84%–98 % positive samples) than in the day-care hospital (40%–72 %). No samples were found above the “action limit” (10000 pg/cm2), but concentrations were frequently above the “safe”/alert level (100 pg/cm2), particularly for cyclophosphamide and ifosfamide (largest campaign's 90th percentiles: 2197 pg/cm2 and 1898 pg/cm2). Despite the approach's nuances, the maximum daily dermal intake calculated (1.6 μg/day, considering a single genotoxic drug) was lower than the acceptable daily intake. This study provided knowledge regarding surface contamination in a European hospital, where occupational exposure to some ADs of concern cannot be ruled out and follow-up monitoring is recommended, even if workers seem unlikely to develop cancer from handling them. Furthermore, this work contributes to the implementation of regular environmental monitoring programs for ADs in Portugal, enhancing compliance with EU recommendations.